Sistem Pendukung Keputusan Mengukur Pencemaran Udara di Kabupaten Pringsewu Metode K-Means - Adi Prasetia Nanda; Ahmad Syarifuddin; M. Islam Mahdi (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2023)
Decision Support System for Measuring Air Pollution in Pringsewu Regency using K-Means Method - The negative impact of residual combustion of motor vehicles or carbon dioxide gas on environmental conditions is causing noise and air pollution. This study aims to measure the level of air pollution caused by the residual combustion of motorized vehicles or carbon dioxide gas. The research data is secondary data obtained from DLH (Environmental Service) data for Pringsewu Regency in 2023 by measuring emission and noise tests on each motorized vehicle and comparing them with measurements taken in 2022. The data was analyzed using the K-Means method of nine Districts in Pringsewu Regency. The results of the calculation measuring air pollution in Pringsewu Regency using the K-Means method, obtained 2 clusters of the entire data, namely: cluster A, which is an area where it is polluted while B is not polluted. The meaning of number 1 is to focus on polluted areas and 0 is an unpolluted area. The sub-districts of Sukoharjo, Adiluwih, and Banyumas are not polluted and the sub-districts of Pringsewu, Pagelaran, Pardasuka, Gadingrejo, Ambarawa, and North Pagelaran are already polluted.